Seaweeds from the Portuguese coast as a source of proteinaceous material: Total and free amino acid composition profile. (15th December 2018) - Vieira, Elsa Ferreira; Soares, Cristina; Machado, Susana; Correia, Manuela; Ramalhosa, Maria João; Oliva-teles, Maria Teresa; Paula Carvalho, Ana; Domingues, Valentina Fernandes; Antunes, Filipa; Oliveira, Teresa Azevedo Cardoso; Morais, Simone; Delerue-Matos, Cristina
Highlights: Total and free amino acid composition of 9 seaweeds from Portuguese coast is given. Tryptophan, methionine and leucine are the limiting essential amino acids (EAA). Brown seaweeds presented lower EAA contents but higher non-EAA levels and flavor AA. Lysine was found in high concentrations, especially in red and green seaweeds. Abstract: The total protein content and the (total and free) amino acid composition of nine edible species of red, brown and green seaweeds collected in the Portuguese North-Central coast were quantified to assess their potential contribution to the recommended dietary intake. Whenever possible, the protein and amino acid composition was compared with that of commercial European seaweeds. The protein content was the highest ( P  < 0.05) in red species (19.1–28.2 g/100 g dw), followed by the green seaweed Ulva spp. (20.5–23.3 g/100 g dw), with the lowest content found in brown seaweeds (6.90–19.5 g/100 g dw). Brown seaweeds presented the lowest mean contents of essential amino acids (EAAs) (41.0% protein) but significantly ( P  < 0.05) higher concentrations of non-essential amino acids (36.1% protein) and free amino acids (6.47–24.0% protein). Tryptophan, methionine and leucine were the limiting EAAs in all species. In contrast, lysine was found in high concentrations, especially in red (2.71–3.85% protein) and green (2.84–4.24% protein) seaweeds.